2013
DOI: 10.15663/tandc.v13i0.10
|View full text |Cite
|
Sign up to set email alerts
|

Key Competencies in secondary school: An examination of the factors associated with successful implementation

Abstract: . It is directed towards a professional audience and focuses on contemporary issues and research relating to curriculum pedagogy and assessment. ISSN 1174-2208 Notes for ContributorsTeachers and Curriculum welcomes:• research based papers with a maximum of 3,500 words, plus an abstract or professional summary of 150 words, and up to five keywords;• opinion pieces with a maximum of 1500 words; and• book or resource reviews with a maximum of 1000 words. FocusTeachers and Curriculum provides an avenue for the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…The research aligns with the findings of Hamilton, Farruggia, Peterson and Carne's (2013) study into the NZC key competency implementation processes and strategies used by 5 economically diverse secondary schools. They identified that the schools that were more successful at integrating the KCs into their curriculum were characterised by a rethinking of pedagogy and teaching practice.…”
Section: Key Competencies Agency and Dispositionalitysupporting
confidence: 71%
“…The research aligns with the findings of Hamilton, Farruggia, Peterson and Carne's (2013) study into the NZC key competency implementation processes and strategies used by 5 economically diverse secondary schools. They identified that the schools that were more successful at integrating the KCs into their curriculum were characterised by a rethinking of pedagogy and teaching practice.…”
Section: Key Competencies Agency and Dispositionalitysupporting
confidence: 71%